2017
DOI: 10.2215/cjn.13221216
|View full text |Cite
|
Sign up to set email alerts
|

CMV and BKPyV Infections in Renal Transplant Recipients Receiving an mTOR Inhibitor–Based Regimen Versus a CNI-Based Regimen: A Systematic Review and Meta-Analysis of Randomized, Controlled Trials

Abstract: We found moderate- to high-quality evidence of reduced risk of cytomegalovirus infection in renal transplant recipients in the mTOR inhibitor-based compared with the calcineurin inhibitor-based regimen. Our review also suggested that a combination of a mTOR inhibitor and a reduced dose of calcineurin inhibitor may be associated with similar eGFR and rates of acute rejections and serious adverse events compared with a standard calcineurin inhibitor-based regimen at the expense of higher incidence of proteinuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 44 publications
4
67
1
3
Order By: Relevance
“…There was no overall effect on opportunistic infections: other studies have suggested that sirolimus may interfere with viral replication and therefore reduce the incidence of cytomegalovirus infections 33, 34. We observed no benefit (or hazard), but there were too few such infections in the 3C Study to make robust inferences.…”
Section: Discussioncontrasting
confidence: 56%
“…There was no overall effect on opportunistic infections: other studies have suggested that sirolimus may interfere with viral replication and therefore reduce the incidence of cytomegalovirus infections 33, 34. We observed no benefit (or hazard), but there were too few such infections in the 3C Study to make robust inferences.…”
Section: Discussioncontrasting
confidence: 56%
“…The authors determined that there was moderate to high-quality evidence to show that an mTOR inhibitorbased regimen was associated with a reduced risk of CMV infection but could not confirm an effect on BK infection. 13 Another report from that institution similarly showed no difference in outcomes at 1 year between TACeverolimus and TAC-MMF cohorts. 14,15 Other reports have noted comparable surgical complication rates to tacrolimus-based immunosuppression and excellent graft survivals.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta‐analysis of renal transplant studies sought to determine whether the use of an mTOR inhibitor vs a calcineurin inhibitor immunosuppressive regimen would influence the risk of either CMV or BK infection. The authors determined that there was moderate to high‐quality evidence to show that an mTOR inhibitor‐based regimen was associated with a reduced risk of CMV infection but could not confirm an effect on BK infection . There are little data on the risk of viral infection after KP transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Several retrospective studies and meta-analyses have shown that mammalian target of rapamycin (mTOR) inhibitors are associated with lower incidence of CMV infection or disease. 4 A recent single center prospective randomized study confirmed these findings in kidney transplant recipients receiving no pharmacological prophylaxis. 5 In this study, patients receiving reduced-dose tacrolimus (TAC) and everolimus (EVR) showed a significant reduction in the incidence of CMV infection/disease compared to standard-dose TAC and sodium mycophenolate (MPS).…”
Section: Introductionmentioning
confidence: 80%
“…Several retrospective studies and meta‐analyses have shown that mammalian target of rapamycin (mTOR) inhibitors are associated with lower incidence of CMV infection or disease . A recent single center prospective randomized study confirmed these findings in kidney transplant recipients receiving no pharmacological prophylaxis .…”
Section: Introductionmentioning
confidence: 93%